Kras as a key oncogene and therapeutic target in pancreatic cancer - Collins, Meredith A.; Pasca Di Magliano, Marina (Frontiers in Physiology, 2014)
Pancreatic cancer is one of the deadliest human malignancies and little progress has been achieved in its treatment over the past decades. Advances in our understanding of the biology of this disease provide new potential opportunities for treatment. Pancreatic cancer is preceded by precursor lesions, the most common of which are known as Pancreatic Intraepithelial Neoplasia (PanIN). PanIN lesions, which are the focus of this review, have a high incidence of Kras mutations, and Kras mutations are a hallmark of the late-stage disease. We now know from genetically engineered mouse models that oncogenic Kras is not only driving the formation of pancreatic cancer precursor lesions, but it is also required for their progression, and for the maintenance of invasive and metastatic disease. Thus, an enormous effort is being placed in generating Kras inhibitors for clinical use. Additionally, alternative approaches, including understanding the role of Kras effector pathways at different stages of the disease progression, are being devised to target Kras effector pathways therapeutically. In particular, efforts have focused on the MAPK pathway and the PI3K pathway, for which inhibitors are widely available. Finally, recent studies have highlighted the need for oncogenic Kras to establish feedback mechanisms that maintain its levels of activity; the latter might constitute alternative ways to target Kras in pancreatic cancer. Here, we will review recent basic research and discuss potential therapeutic applications.